1991
DOI: 10.1063/1.859759
|View full text |Cite
|
Sign up to set email alerts
|

Soliton propagation, collision, and reflection at a sheath in a positive ion–negative ion plasma

Abstract: Experiments on the propagation and collision of a Korteweg-deVries soliton in a positive ionnegative ion plasma are described. Both a one-dimensional overtaking collision and a twodimensional resonant collision are examined. Soliton propagation into a steady-state plasma sheath created by an additional biased metal plate in such a plasma is large enough that the detailed soliton motion in the locally inhomogeneous plasma can be easily studied. A partial reflection and partial transmission of the soliton at a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…For example, we obtained that the phase velocity and amplitude of the reflected soliton are always less than those of the incident one. This is consistent with the results of Cooney et al 20 Another result that the fast mode velocity and the amplitude of incident soliton increase with the negative ion density is similar to the one obtained by them in different experiment. 17 In order to make a further comparison we have plotted in Fig.…”
Section: Comparison With Experimental Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For example, we obtained that the phase velocity and amplitude of the reflected soliton are always less than those of the incident one. This is consistent with the results of Cooney et al 20 Another result that the fast mode velocity and the amplitude of incident soliton increase with the negative ion density is similar to the one obtained by them in different experiment. 17 In order to make a further comparison we have plotted in Fig.…”
Section: Comparison With Experimental Resultssupporting
confidence: 93%
“…In addition to the soliton reflection in ordinary plasmas, the propagation of ion acoustic solitons [16][17][18][19] and their reflection [20][21][22][23] in an unmagnetized inhomogeneous plasma having both the positive and negative ions has been reported. For studying the soliton reflection problem theoretically, modified KdV equations for incident and reflected solitons were derived using the reductive perturbation analysis and then solved after their coupling.…”
Section: Introductionmentioning
confidence: 99%
“…This case occurs also in the collision of two KdV solitons. Cooney et al [40] studied the overtaking collision, to verify the KdV soliton nature of an observed signal in the plasma experiment.…”
Section: Mechanism and Rules Of Collision Of The Microscopic Particlementioning
confidence: 94%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Linear ion acoustic waves were reflected from a positively biased solid metallic plate. 9 KdV solitons were reflected from a negatively biased metal plate.…”
Section: Introductionmentioning
confidence: 99%